Phylogenetic and recombination analysis of the herpesvirus genus varicellovirus - Kolb, Aaron W. (BMC Genomics, 2017)
BACKGROUND: The varicelloviruses comprise a genus within the alphaherpesvirus subfamily, and infect both humans and other mammals. Recently, next-generation sequencing has been used to generate genomic sequences of several members of the Varicellovirus genus. Here, currently available varicellovirus genomic sequences were used for phylogenetic, recombination, and genetic distance analysis. RESULTS: A phylogenetic network including genomic sequences of individual species, was generated and suggested a potential restriction between the ungulate and non-ungulate viruses. Intraspecies genetic distances were higher in the ungulate viruses (pseudorabies virus (SuHV-1) 1.65%, bovine herpes virus type 1 (BHV-1) 0.81%, equine herpes virus type 1 (EHV-1) 0.79%, equine herpes virus type 4 (EHV-4) 0.16%) than non-ungulate viruses (feline herpes virus type 1 (FHV-1) 0.0089%, canine herpes virus type 1 (CHV-1) 0.005%, varicella-zoster virus (VZV) 0.136%). The G + C content of the ungulate viruses was also higher (SuHV-1 73.6%, BHV-1 72.6%, EHV-1 56.6%, EHV-4 50.5%) compared to the non-ungulate viruses (FHV-1 45.8%, CHV-1 31.6%, VZV 45.8%), which suggests a possible link between G + C content and intraspecies genetic diversity. Varicellovirus clade nomenclature is variable across different species, and we propose a standardization based on genomic genetic distance. A recent study reported no recombination between sequenced FHV-1 strains, however in the present study, both splitstree, bootscan, and PHI analysis indicated recombination. We also found that the recently sequenced Brazilian CHV-1 strain BTU-1 may contain a genetic signal in the UL50 gene from an unknown varicellovirus. CONCLUSION: Together, the data contribute to a greater understanding of varicellovirus genomics, and we also suggest a new clade nomenclature scheme based on genetic distances. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12864-017-4283-4) contains supplementary material, which is available to authorized users.